The impact of bilateral trade and foreign direct investment on Malaysia’s economic growth: The role of Singapore - Wong, Chee Yie; Yow, Hui Fang (2018)
Open economy is essential for a sustainable economic growth in a country. In recent years, Malaysia is actively promoting economic integration to improve innovation and productivity outputs to become a high-income nation. Singapore is the top ASEAN trading and investment partner of Malaysia and both countries have bilateral ties with each other since 1965s. This research study analyzes the impact of Malaysia bilateral trade and investment with Singapore on Malaysia’s economic growth from 2008 to 2016. Vector error correction model (VECM) estimation reveals that Malaysia exports to Singapore and Malaysia outward foreign direct investment in Singapore have significant relationship with Malaysia’s economic growth. On the other hand, Malaysia imports from Singapore and Malaysia inward foreign direct investment by Singapore have insignificant relationship with Malaysia’s economic growth. The results also show that Malaysia exports to Singapore is significantly positive towards Malaysia’s economic growth and Malaysia outward foreign direct investment in Singapore is significantly negative towards Malaysia’s economic growth. This concludes that only Malaysia exports to Singapore can help to increase Malaysia’s economic growth.